Penilaian Kepuasan Penghuni Perumahan Menggunakan Gap Analysis: Studi Kasus di Kota Naypyitaw, Myanmar - Phyu, Pan Ei; Effendi, Nursyirwan; Purnawan, Purnawan (Universitas Kristen Maranatha, 2024)
This research paper conducts an evaluation of residential satisfaction within government-provided four-storied apartment complexes situated in civil-servant housing areas in Naypyitaw City, Myanmar. As the construction of these apartment buildings continues to address the housing demands of civil servants, comprehending the determinants of residents' contentment becomes paramount. The study encompasses data collected from 500 households through structured questionnaires employing a multi-cluster sampling approach. These questionnaires utilize a five-point Likert Scale format to gauge residents' levels of importance and satisfaction. Gap Analysis is employed to scrutinize the gathered data, ultimately identifying seven pivotal attributes that hold the potential to substantially enhance residential satisfaction. These attributes encompass ceiling height, apartment layout plan, room and corridor dimensions, quantity of rooms, staircase design, neighborhood relations, and proximity to police stations. Based on these revelations, recommendations are tendered, advocating the modification and reevaluation of these attributes in forthcoming housing developments. This underscores the imperative need for creating a livable city by ensuring the provision of essential services in closed proximity to residential areas.